Patent Infringement in Personalized Medicine: Limitations of the Existing Exemption Mechanisms - Jiyeon Kim (Washington University Law Review, 2018)
Mr. X suffers from recurrent glioblastoma, a type of deadly brain cancer. One of his physicians reads a study reporting a novel immunotherapy, which uses the chimeric antigen receptor T cell (CAR-T) technology, leading to regression of glioblastoma in a small number of patients. Although the therapy has recently been approved by the U.S. Food and Drug Administration (FDA) and is now offered by two major pharmaceutical companies, it is only approved for certain hematological cancers. In addition, Mr. X’s cancer does not express the biomarker that is necessary for the CAR-T therapy used in the published glioblastoma trial. Fortunately, the physicians are aware of a research laboratory at the university associated with the medical center that has expertise on the technologies associated with the CAR-T immunotherapy as well as certain biomarkers associated with Mr. X’s cancer. In collaboration with the laboratory’s researchers, Mr. X’s physicians conduct a small clinical trial administering an experimental CAR-T therapy to Mr. X and other glioblastoma patients, for whom this clinical trial was their only remaining hope. Later, one of the pharmaceutical companies holding multiple CAR-T patents sues the physicians, researchers, and academic institution for patent infringement. This hypothetical scenario involving the first FDA-approved gene therapy, CAR-T therapy, illustrates a potential patent infringement lawsuit that might occur more frequently as we enter the new era of personalized and precision medicine. The beauty and power of personalized medicine is that it is inherently experimental and innovative. Naturally, therapies in personalized medicine are built upon many patented technologies. Thus, underlying these novel therapies is the potential for alleged patent infringement by the physicians and researchers who experiment with and personalize the therapy in order to cure patients and save their lives. This Note uses the CAR-T therapy as a case study to examine the unique challenges that patent law faces in the dawn of the personalized medicine era, particularly regarding patent infringement. Specifically, this Note inquires whether a use of patented medical therapy related to a clinical experiment or trial by physicians, researchers, and academic institutions for the purpose of patient treatment renders them liable for patent infringement. Patent law confers exclusive rights to inventors and allows them to enforce those rights associated with a specific patent by bringing a patent infringement claim against the alleged infringer. At the same time, however, patent law also permits certain unauthorized uses of patented inventions to be exempted from infringement challenges or infringement liability. There are two key defenses under which an alleged infringer can be exempted: one provides exemption largely based on the status of the alleged infringer (“medical procedure exemption”) and the other based on the nature or purpose of the alleged infringing use (“experimental use exemption”). This Note analyzes whether the two exemptions indeed provide effective immunity from patent infringement or infringement liability for physicians, researchers, and academic institutions involved in the use of experimental therapies in the personalized medicine era. Analysis of the statutory text, legislative history, and case law of the medical procedure exemption reveals that the “biotechnology patents” exception renders the provision ineffective for infringement lawsuits involving CAR-T therapy. Therefore, this Note argues that the medical procedure exemption is incompatible with the personalized medicine era. Meanwhile, the experimental use exemption bifurcates into a narrow common law doctrine and a statutory provision that is interpreted relatively broadly when related to FDA submission. However, it is ambiguous whether a clinical trial would be considered as an “experimental use” under the narrow common law experimental use doctrine and whether the statutory experimental use exemption would permit uses that might not have any realistic potential for FDA submission. While many scholars have argued for a broad experimental use doctrine, the discussions have remained largely in the context of basic science. This Note presents a novel argument for a broad experimental use doctrine in the context of personalized medicine and suggests that the new era of personalized medicine calls for an additional factor in the experimental use analysis—clinical trials and experiments that cure and save patients’ lives. Part I provides an overview of the CAR-T immunotherapy as a model therapy representing personalized medicine and presents the issue of patent infringement. Part II examines the medical procedure exemption and analyzes its effectiveness as a defense to patent infringement liability involving CAR-T patents. Then, Part III turns to the experimental use exemption, examines its effectiveness for providing immunity from CAR-T patent infringement, and concludes by arguing for a broader experimental use doctrine for the personalized medicine era.
Keywords: Patent law; Patent Infringement; Personalized Medicine; Food and Drug Administration; FDA; USFDA; chimeric antigen receptor T cell; CAR-T; technology; immunotherapy; biomarkers; therapy; precision medicine; medical procedure exemption; experimental use exemption; biotechnology; 21st Century Cures Act of 2016; Precision Medicine Initiative; Gene Therapy; 35 U.S.C. § 287(c); 35 U.S.C. § 271(e)(1)